0500 Increased adherence to light therapy and psychosocial outcomes in adolescents and young adults with cancer. (25th May 2022) - MacArthur, Erin; Semko, Joshua; Kamara, Dana; Wang, Fang; Pan, Haitao; Brigden, Jane; Pappo, Alberto; Wilson, Matthew; Crabtree, Valerie
Abstract: Introduction: Adolescent/young adult (AYA) oncology patients consistently report fatigue as one of the most distressing symptoms during treatment. Bright white light (BWL) has been demonstrated to improve the symptoms of cancer-related fatigue in adults, and our prior research demonstrated feasibility, acceptability, and preliminary efficacy of BWL in AYA with cancer. As part of the trial examining the feasibility and acceptability of BWL in AYA, we explored whether adherence affected patient outcomes in the BWL group. Methods: Twenty-seven participants were randomized to receive BWL using LiteBook® (retrofitted with adherence monitors) for 30 minutes upon waking daily for eight weeks. Study team members met with patients weekly for the duration of the intervention to download adherence data from the monitors, administer questionnaires, and discuss barriers to adherence if necessary. Participants completed mood, quality of life, and fatigue measures at every other research visit (5 times over the duration of the study). Results: Adherence was characterized by total number of days that participants used the light device while on study. Multivariate regression was used to examine the predictive relationship between adherence and patient outcomes. Adherence significantly predicted parent-reported physical functioning [β=1.45, p= 0.0079], emotional functioning [β=0.87, p=0.0137], and total health-related quality of life [β= 0.76, p= 0.0218]. Adherence did not predict any of the self-reported patient outcomes. Conclusion: BWL is a promising treatment to improve cancer-related fatigue in AYA, and adherence is essential to treatment success. Although adherence did not predict any participant self-reported outcomes, participants with better adherence had improved parent-reported emotional and physical functioning and overall quality of life. Individually tailored interventions, including sleep hygiene psychoeducation and motivational interviewing, may be used to increase adherence to light therapy to improve patient outcomes. Measures to monitor and foster adherence should be included in future light therapy trials. Support (If Any): This research was funded and supported by ALSAC.